(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The urgency of the problem of acute coronary pathology is determined by the growing incidence of coronary artery disease (CHD), high mortality from this disease, as well as the difficulties of timely diagnosis and differential diagnosis of exacerbations of coronary heart disease. Cardiovascular diseases occupy the first place in the structure of mortality and disability of the population. One of the forms of complications of coronary heart disease is acute myocardial infarction (AMI). AMI is one of the most threatening and life-threatening conditions in cardiology. A significant part of deaths is caused by AMI [5]. Myocardial infarction (MI) is an important medical, social and economic problem for highly developed countries due to its prevalence, mortality, and temporary and permanent disability. Among the factors affecting life expectancy and mortality in MI, acute heart failure, cardiac arrhythmias, and repeated coronary attacks are the most serious. Heart failure increases the risk of early and long-term mortality associated with MI. In patients with acute coronary syndrome and signs of heart failure, the risk of death in a hospital setting increases 4-fold [12]. In recent years, it has become generally accepted that the most real factor in both the initiation and progression of atherosclerosis and the development of its acute clinical manifestations is inflammation, and the destabilization of atherosclerotic plaque is determined by the high activity of the chronic inflammatory process in it [11]. Of great interest is the study of specific markers of inflammation, cytokines, which may be more predictively significant in determining the processes associated with the destabilization of vascular atherosclerosis. There are a number of cytokines whose action is associated with the activation of inflammation in the atherosinflammatory plaque. Some of them, for example, tumor necrosis factor α (TNF-α), interleukin-1b (IL-1b), IL-6, have pro-inflammatory properties, while others, in particular IL-10, are associated with anti-inflammatory reactions [8,9].